Procurement performance improvement: A case study of non-profit organization in Myanmar - Lwin, Hnin Wai; Puttibarncharoensri, Piyawan; Elango, Dinesh; Jiratchot, Chanita; Smutkupt, Srobol (Journal of Management, Economics, and Industrial Organization, 2022)
Supply chain management is a critical process for a humanitarian organization to fulfill the requirement of targeted beneficiaries who need assistance for their daily life to access foods, shelters, water & sanitation, etc. This research is about a non-profit organization that has been facing poor supply chain performance for the food procurement process in the targeted area of offices. This issue is a sensitive case for the organization to show the transparency of the process, the performance of the procurement process and accountability to donors. According to historical data from January 2017 to December 2018, there are 12 procurement cases (tender) were conducted by the two offices. Data were analyzed and the average total lead time of the current food procurement process is 41 days which is over than standard time as in policy. To overcome this issue the researcher applied Value Stream Mapping (VSM) Methodology for the improvement of process value-added time and to reduce the total lead time of the process in order to finish within the suggested time frame. The VSM methodology was applied to identify the wastes (non-value-added activities) and their root causes by applying causes and effects analysis in the process of tender from reviewing purchase to the payment process. Then, a work plan developed and applied in the current process during the specific period, and after that, the researcher tested the pilot test whether the work plan is effective to achieve a good procurement process or not. To monitor the future process, a performance measurement plan was developed for the continuous improvement of the process performance of an organization.